Spatiotemporal Dynamics of Land Cover in Taji District: A Remote Sensing Approach - Khaleefa, Ahmed A.; Khudair, Yasser Y.; Hasan, Ahmed F. (Iraqi Journal of Science, 2025)
This study aims to reveal the extent of buildings and urbanization increases in the Taji district. The Taji District faces a problem in determining the judiciary's direction from an area of a rural nature to an area of a civil nature. The importance of this study lies in shedding light on the problem of lack of urban planning that occurs on the outskirts of urban cities in general and in Baghdad in particular. Taji District is located within Baghdad Governorate, one of the governorates of Iraq. Satellite images from Landsat 7 for 2003, 8 for 2014, and 9 for 2023 were acquired to cover the study area. Each image was cropped according to the administrative boundaries of the Taji region. Each image was cropped according to the administrative boundaries of the Taji region using the QGIS program, and the ENVI program was used for classification and statistical operations. The maximum likelihood classification was chosen as the main classifier to distinguish different land cover types in the study region. The areas of each feature of the image were calculated, and then the percentage of each feature was calculated. The graphical relationship between time in years and urban areas during each year showed that urbanization increases at a constant rate, which is the constant increase in urban area and equals 1.06% for each year. This increase is considered relatively high since the Taji district is considered a rural agricultural area, and the explanation for the change in this percentage is due to several reasons, the most important of which is the increase in population and lack of water resources.